2017
DOI: 10.5947/jeod.2016.005
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Degeneration Thesis: the Role of Democracy in Worker Cooperatives?

Abstract: This paper uses data collected through written narratives, focus groups and participant observation in three small UK worker cooperatives to investigate the role of democracy in maintaining cooperatives' dual social-economic characteristic and resisting degeneration. More specifically, it adds to limited empirical literature countering the degeneration thesis by arguing that ongoing processes of individual-collective alignment, understood as central to the practice of democracy, help cooperatives to: balance v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
1
35
0
2
Order By: Relevance
“…Other authors have focused on the processes and conditions that lead cooperatives to retain their egalitarian democratic functioning over time and avoid degeneration, highlighting their ability to balance the conflicting logics and aims of market-embedded demand for organizational efficiency on the one hand, and culturally-embedded values for inclusive engagement and democracy on the other (Varman and Chakrabarti 2004, Hernandez 2006, Langmead 2016, Jaumier 2017. In addition, a smaller but growing line of research has highlighted cooperatives' potential to regenerate; that is, to revive cooperative values and re-assemble democratically-structured forms of decision making as a reaction to degeneration (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have focused on the processes and conditions that lead cooperatives to retain their egalitarian democratic functioning over time and avoid degeneration, highlighting their ability to balance the conflicting logics and aims of market-embedded demand for organizational efficiency on the one hand, and culturally-embedded values for inclusive engagement and democracy on the other (Varman and Chakrabarti 2004, Hernandez 2006, Langmead 2016, Jaumier 2017. In addition, a smaller but growing line of research has highlighted cooperatives' potential to regenerate; that is, to revive cooperative values and re-assemble democratically-structured forms of decision making as a reaction to degeneration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, meanwhile, have demonstrated that cooperatives and other member-based organizations can resist degeneration and achieve a healthy balance between oligarchy and democracy by both maintaining their original nature in the long term and revitalizing their democratic functioning over time (Ng and Ng 2009, Storey et al 2014, Narvaiza et al 2017. A variety of mechanisms are highlighted, including the reenactment of a democratic discourse that countervails the dominant market rhetoric (Eikenberry 2009); the reproduction of an active membership through careful selection of managers and workers and their socialization into cooperative values (Chaves and Sajardo 2004); the permanent requirement for accountability and endless overt critique of managers to circumvent the coalescence of power in their hands (Jaumier 2017); the organization of labor to reinforce a participatory culture grounded in self-determination, horizontality and solidarity (Hernandez 2006); connection to wider social movements to promote community-based goals (Diamantopoulos 2012, Langmead 2016, and the eventual 'remutualization' of cooperatives (Sousa and Herman 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the so called "degeneration thesis" has recently come under scrutiny. The argument is that degeneration is not inevitable and that cooperatives can also regenerate themselves [53,54].…”
Section: Sse and Its Own Particular Tensionsmentioning
confidence: 99%
“…As Vieta argues, 'autogestión in the new cooperativism, to be sure, is not a ready-made solution for liberation from capitalist exploitation', since 'it remains always at tension within the existing capitalist economic status-quo and its supportive state apparatus' (Vieta 2014, p. 800). Worker co-ops that explicitly challenge capitalist ideals also compete within the capitalist market economy in order to survive, and can thus be understood as positioned in a rivalry between self-determination of radical democracy and economic market mechanisms of global capitalism (Diamantopoulos 2012, Langmead 2016.…”
Section: Introductionmentioning
confidence: 99%